Service Life Analysis of Underground Cables Using PI and DAR Methods - Giovanni Dimas Prenata; Mohammad Eriko Ramadhani; Reza Sarwo Widagdo (Jurnal JEETech, 2026)
This study examines the insulation resistance of underground conductors connecting 3-phase induction motors that drive pump machines. The results of the insulation resistance measurements were analyzed using the Polarization Index (PI) method and the Dielectric Absorption Ratio (DAR) method. There are 3 areas of conductor cables analyzed to calculate the remaining life of each conductor cable. For area 1, the remaining life of the inter-phase conductor cable is R-S 20.9 years, S-T 20.5 years T-R 20.8 years. Area 2, the remaining life of the inter-phase conductor cable is R-S 20.6 years, S-T 20.7 years T-R 21.1 years. For area 3, the remaining life of the inter-phase conductor cable is R-S 16.5 years, S-T 14 years T-R 15 years.